A Germline Variant at 8q24 Contributes to the Serum p2PSA Level in a Chinese Prostate Biopsy Cohort - Lin, Xiaoling; Wu, Yishuo; Liu, Fang; Na, Rong; Huang, Da; Xu, Danfeng; Gong, Jian; Zhu, Yao; Dai, Bo; Ye, Dingwei; Yu, Hongjie; Jiang, Haowen; et al. (Frontiers in Oncology, 2021)
Introduction The clinical performance of [–2]proPSA (p2PSA) and its derivatives in predicting the presence and aggressiveness of prostate cancer (PCa) has been well evaluated in prostate biopsy patients. However, no study has been performed to evaluate the common genetic determinants that affect serum level of p2PSA. Materials and Methods Here, we performed a two-stage genome-wide association study (GWAS) on the p2PSA level in Chinese men who underwent a transperineal ultrasound-guided prostate biopsy at Huashan Hospital, Shanghai Cancer Center, and Ruijin Hospital in Shanghai, China. Germline variants significantly associated with the p2PSA level in the first stage (n = 886) were replicated in the second stage (n = 1,128). Multivariate linear regression was used to assess the independent contribution of confirmed single nucleotide polymorphisms (SNPs) and known covariates, such as age, to the level of p2PSA. Results A novel non-synonymous SNP, rs72725879, in region 8q24.21 of the PRNCR1 gene was significantly associated with the serum level of p2PSA in this two-stage GWAS (p = 2.28 × 10−9). Participants with homozygous “T” alleles at rs72725879 had higher p2PSA levels compared to allele “C” carriers. This variant was also nominally associated with PCa risk (p-combined = 3.44 × 10−18). The association with serum level of p2PSA was still significant after adjusting for PCa risk and age (p = 0.017). Conclusions Our study shows that the genetic variants in the 8q24.21 region are associated with the serum level of p2PSA in a large-scale Chinese population. By taking inherited variations between individuals into account, the findings of these genetic variants may help improve the performance of p2PSA in predicting prostate cancer.